Has the introduction of antibiotic-impregnated external ventricular drain catheters changed the nature of the microorganisms cultured in patients with drain-related infection? A single neurosurgical centre's experience. (2nd September 2016) - Talibi, S.; Tarnaris, A.; Shaw, S. A.
Abstract: Background: The introduction of antibiotic-impregnated catheters (AICs) has significantly reduced external ventricular drain (EVD) infection rates, inhibiting in particular Gram-positive microbial infection. There is a theoretical increased risk of selection of resistant and Gram-negative microorganisms. The aim of this study is to look at the impact of the introduction of AICs on microorganism susceptibility of infected EVDs and to determine whether the use of such devices results in shift from Gram-positive to Gram-negative microorganisms. A secondary aim is to determine if a change in routine empiric antimicrobial therapy is required because of a change in the microorganism(s) causing infection. Methods: Retrospective analysis of EVDs inserted as a primary procedure or part of a concomitant neurosurgical procedure in 2006 (pre-AIC) and 2012 (post-AIC Codman Bactiseal © impregnated with clindamycin 0.15% and rifampicin 0.054%). EVD-related infection was defined as a cerebral spinal fluid sample with a positive culture with some patients having one or more microorganisms infecting the same EVD at the same time. Sixty-five EVDs over 843 days and 66 EVDs over 619 days were inserted respectively in each cohort. Results: In 2006, 9 of 35 patients developed EVD-related infection and 13 microorganisms were cultured; 8 of which were Gram-positive and 4 Gram-negative. Four of 49 patients developed EVD-related infection in 2012 and six microorganisms were cultured; four Gram-positive and two Gram-negative. The cumulative incidence of EVDs becoming infected is 18.5% (12/65) and 6.1% (4/66; p = 0.03) in 2012. The EVD-associated infection rate was 14.2 per 1000 EVD days and 6.5 per 1000 EVD days in 2012. There was no change in mortality. Conclusions: The study demonstrates that within a single neurosurgical centre there have been neither changes in susceptibility of microorganisms nor a change from predominately Gram-positive to Gram-negative microorganisms infecting EVDs following the switch to AIC. The infection rate has significantly reduced due to change in catheter type.